2019
DOI: 10.3892/ijmm.2019.4248
|View full text |Cite
|
Sign up to set email alerts
|

Effect of HMGB1 and RAGE on brain injury and the protective mechanism of glycyrrhizin in intracranial‑sinus occlusion followed by mechanical thrombectomy recanalization

Abstract: The key to successful treatment of cerebral venous-sinus occlusion (CVO) is the rapid recanalization of the sinus following venous-sinus occlusion; however, rapid recanalization of the sinus may also cause secondary cerebral injury. The present study examined mechanical thrombectomy-related brain injury and the possible molecular mechanisms following CVO recanalization, and investigated the protective effect of glycyrrhizin (GL) in CVO recanalization. The cerebral venous sinus thrombosis (CVST) model was induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Owing to the difficulty of delivering these two ferroptosis inhibitors across the blood–brain barrier, their clinical applications to CNS diseases are limited [ 18 , 21 ]. GL, a major constituent of licorice root, has been demonstrated to pass through the blood–brain barrier and exert a neuroprotective effect when administered by intraperitoneal injection [ 22 ]. The protective effect of GL against mitochondrial injury and oxidative stress has also been confirmed in pathological conditions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the difficulty of delivering these two ferroptosis inhibitors across the blood–brain barrier, their clinical applications to CNS diseases are limited [ 18 , 21 ]. GL, a major constituent of licorice root, has been demonstrated to pass through the blood–brain barrier and exert a neuroprotective effect when administered by intraperitoneal injection [ 22 ]. The protective effect of GL against mitochondrial injury and oxidative stress has also been confirmed in pathological conditions [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizin (GL) is a natural glycosyl triterpenoid product and is recognized as an inhibitor of high-mobility group box 1 (HMGB1) [ 22 ]. HMGB1 is a ubiquitous transcription factor that is involved in the maintenance of nucleosome structure, chromatin remodeling, and the regulation of DNA recombination and repair [ 23 – 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have reported a relationship between inflammation and venous thrombosis. [ 46 48 ]. One in vivo noted that neutrophils contribute to the initiation of thrombosis [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…High mobility group box 1 (HMGB1), a member of the damage-associated molecular pattern molecular family, is recently reported to be implicated in the inflammatory cascade-amplification reaction in the pathophysiology of CVT ( 67 ). Under normal physical conditions, HMGB1 exists in the nucleus and maintains the chromosomal structure and physiological activities of the DNA ( 99 ).…”
Section: Inflammation In Cerebral Venous Thrombosis-related Brain Damagementioning
confidence: 99%
“…On suffering inflammatory stimuli, HMGB1 is released into the extracellular space and immediately activates the innate immune response ( 99 ). Independently, HMBG1 can activate its downstream mediator, the receptor for advanced glycated end products (RAGE), to induce endocytosis and generate proinflammatory factors such as TNF-α, IL-1β, and IL-6 ( 67 ). The inhibition of HMGB1 and RAGE can reduce the expression of downstream inflammatory factors and attenuate CVT-mediated further damage ( 67 ).…”
Section: Inflammation In Cerebral Venous Thrombosis-related Brain Damagementioning
confidence: 99%